Pengaruh Pemeriksaan Pajak Dan Kepatuhan Wajib Pajak Terhadap Penerimaan Pajak Pada KPP Penanaman Modal Asing Enam Tahun Pajak 2016-2020 - Khairuzain Pratama Elipen; Ajat Sudrajat (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study was conducted to identify the effect of tax audits and taxpayer compliance on tax revenues at the Tax Service Office of Foreign Investment Six for the 2016-2020 tax year. This study used a quantitative approach. The type of data in this study is secondary data obtained from observations of 60-months’ time series data over a 5 year period, namely January 2016 - December 2020. The data was then analyzed using multiple linear regression analysis techniques. The sample selection technique used was a total sampling technique, in which all members of the population, namely 60-months’ time series data, were used as research samples. Data processing was done using SPSS software. The results showed that partially tax audits have a positive and significant effect on tax revenues at the Tax Service Office of Foreign Investment Six, and taxpayer compliance partially has a positive and significant effect on tax revenues at the Tax Service Office of Foreign Investment Six'. Simultaneously, tax audits and taxpayer compliance have a significant effect on tax revenues at the Tax Service Office of Foreign Investment Six